Index Card Match With QR Code Card To Strengthen Students' Learning Motivation - Yulia, Yulia; Astria, Nani; Krismanto, Wawan (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
This study aims to determine the improvement of the learning process and student learning motivation through the index card match (ICM) learning model with QR code cards. The approach to this research is qualitative with the type of classroom action research. The focus of the study is the learning process and student learning motivation. One teacher and 15 students at fifth-grade UPTD SD Negeri 57 Parepare were the study subjects. Data collection techniques were in the form of observation, questionnaires, and documentation. The research instruments were observation sheets, reflection sheets, and student learning motivation questionnaires. Data were analyzed through condensation, presentation, and drawing conclusions or verification. The study's results showed that various changes in the learning process occurred through ICM with QR code card games. Students' enthusiasm was seen during learning; they became more actively involved, showed good collaboration with their group friends, and showed self-confidence. In the first and second cycles, there was no significant increase in learning motivation, and in the third cycle, 75% of students were in the Good or Very Good category. The conclusion is that using the ICM learning model with QR Code Cards can improve learning and student motivation.